Komparasi Profitabilitas Usahatani Padi Sawah Tadah Hujan Kabupaten Barru - Arifin, Arifin; Fattah, Muhammad Arifin; Pata, Abdul Asis; Azisah, Azisah; Sadat, Mohammad Anwar (Universitas Galuh, 2024)
The best or maximum income is achieved when the production level is optimal. Farmer income is one of the motivations for farmers to carry out their farming business. Profitability or farmer income and supported by good farming feasibility through the large ratio of income to farming costs. This research aims to analyze the comparative income, feasibility, and profitability of rainfed lowland rice farming. This research was conducted in Sape'e and Coppo Villages, Barru District, and Lompo Tengah and Lempang Villages, Tanete Riaja District, Barru Regency. The total population of the study was 367 people, while the sample of farmers who were used as respondents was 70 people. To get the number of samples a multi-stage cluster random sampling technique. Data collection techniques used are observation/observation, interviews, and documentation. Data sources in this research are primary data and secondary data. The data analysis method used is quantitative descriptive analysis and profitability with an independent sample t-test. The results showed that the income from rainfed lowland rice farming in the Tanete Riaja District was greater than that of the Barru District. Meanwhile, feasibility and profitability (Net Farm Income, Return on Investment, and Break Event Point) do not have a big difference between Barru District and Tanete Riaja District. Rice farming income in the research area still needs to be increased by reducing production input costs and the government must maintain subsidies for production inputs, especially fertilizer. With this subsidy, fertilizer use as recommended can be carried out to increase the production produced by farmers.